2009
DOI: 10.1007/s00468-009-0370-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation and decrease on free polyamines is associated with the embryogenic capacity of Pinus nigra Arn. cell culture

Abstract: Embryogenic cell lines initiated from immature zygotic embryos of Pinus nigra Arn. ssp. Austriaca were characterized in terms of macromorphological traits (colour, bipolar structures formation, germination ability) and their embryogenic potential was defined as high, medium or null. Quantification of global genomic DNA methylation revealed the existence of specific DNA methylation levels for the determinated embryogenic potentials. The line considered as effectively embryogenic, i.e., with the ability of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 42 publications
4
45
2
4
Order By: Relevance
“…In line with this postulate, we observed a significantly decreased level of 5 mC in the embryogenic culture of Arabidopsis and the reduction in the DNA methylation level has also been associated with SE induction in other plants (Santos and Fevereiro 2002;Xu et al 2004;Noceda et al 2009;Rodríguez-Sanz et al 2014;Teyssier et al 2014). However, in some plants, an increased (Fraga et al 2012;Rival et al 2013), differentially modulated (Leljak-Levanić et al 2004;Nic-Can et al 2013) and steady (Parra et al 2001) level of DNA methylation during SE has been reported.…”
Section: Se Induction Is Associated With the Decreased Level Of Globasupporting
confidence: 84%
“…In line with this postulate, we observed a significantly decreased level of 5 mC in the embryogenic culture of Arabidopsis and the reduction in the DNA methylation level has also been associated with SE induction in other plants (Santos and Fevereiro 2002;Xu et al 2004;Noceda et al 2009;Rodríguez-Sanz et al 2014;Teyssier et al 2014). However, in some plants, an increased (Fraga et al 2012;Rival et al 2013), differentially modulated (Leljak-Levanić et al 2004;Nic-Can et al 2013) and steady (Parra et al 2001) level of DNA methylation during SE has been reported.…”
Section: Se Induction Is Associated With the Decreased Level Of Globasupporting
confidence: 84%
“…Similarly, contents of PAs (higher Spd than Put levels) could be used as criteria for the physiological characterization of somatic embryogenesis in Pinus nigra Arn. (Noceda et al, 2009). Furthermore, the important role of cellular levels of metabolically active free PAs, especially contents of Spd, was shown to be essential for preservation of embryogenic potential of Norway spruce cultures after cryopreservation (Vondráková et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Samples were collected before the induction (day 0, prior to induction) and during induction (days 1,3,7,15,30,45). Three replicates were made each day, each of which consisted of segmented stems from different individuals on the corresponding sampling day.…”
Section: Msapmentioning
confidence: 99%
“…It has been observed that the decrease in DNA methylation is related to the developmental process [7] [63] [64] [65] [66].…”
Section: Dynamics Of Dna Methylation Patterns During Se Inductionmentioning
confidence: 99%